Wspieranie finansowe i promocja bezpośrednich inwestycji zagranicznych w Malezji - Kuźmińska, Aleksandra (Financial Incentives and Promotion of Foreign Direct Investment in Malaysia, 2008)
The Asian region is a very attractive place to locate foreign direct investment (FDI). The leaders in attracting FDI in the region are China, Hong Kong, Singapore, and India. Malaysia does not absorb as much FDI as those countries. Malaysian government tries to change this situation by creating an investment-friendly environment. This article presents two factors that might influence investors' decisions in Malaysia: investment incentives and investment promotion. Malaysia puts lots of effort to offer competitive incentives and efficient FDI promotion programme but it must remember that those factors can be just an addendum to political stability and transparent investment environment. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 147-157